Factors Considered in the New Indonesian 2013 Curriculum Development - Fauzi Rahman Kosasih (ENGLISH, 2015)
This study aimed at investigating factors considered in the new Indonesian 2013 Curriculum development. Qualitative case study was selected as the research design for this study. The data was collected from a document released by Indonesian Minister of Education and Culture in 2013. Document analysis was utilized as the instrument of data collection in this study. The findings revealed that there are five issues considered in the new Indonesian 2013 Curriculum development.